Fishing Effort and Associated Catch per Unit Effort for Small-Scale Fisheries in the Mozambique Channel Region: 1950–2016 - Zeller, Dirk; Vianna, Gabriel M. S.; Ansell, Matthew; Coulter, Angie; Derrick, Brittany; Greer, Krista; Noël, Simon-Luc; Palomares, Maria L. Deng; Zhu, Audrey; Pauly, Daniel (Frontiers in Marine Science, 2021)
The Mozambique Channel region in East Africa has diverse marine ecosystems and serves as a migratory corridor for economically important species. Local and foreign industrial fisheries operate in the Mozambique Channel, but local small-scale fisheries are the crucially important fisheries that provide food-security, livelihoods and economic opportunities for rural coastal communities. This study reconstructed and investigated trends in the fishing effort and catch per unit effort (CPUE) of small-scale marine fisheries in the four Exclusive Economic Zones (EEZs) that constitute the Mozambique Channel, i.e., Union of Comoros, Madagascar, Mayotte and Mozambique, from 1950 to 2016. Effective fishing effort for small-scale fisheries in the form of fishing capacity in kWdays (i.e., kilowatt days) was derived using the number, length, motorization (engine power) by fishing vessels as well as an approximate human-powered equivalent for shore-based fishers without vessels, as well as days of fishing per year. Effective small-scale fishing effort in the Mozambique Channel increased by nearly 60 times from just over 386,000 kWdays in 1950 to over 23 million kWdays in 2016. Correspondingly, the overall small-scale CPUE, based on previously and independently reconstructed catch data declined by 91% in the region as a whole, from just under 175 kg·kWday-1 in the early 1950s to just over 15 kg·kWday-1 in recent years. All four countries showed strongest declines in the small-scale CPUE in the earlier decades, driven by motorization and growth in vessel numbers impacting effective fishing effort. Increased motorization combined with a substantial growth in overall vessel numbers were the drivers of the increasing fishing effort and decreasing CPUE, and clearly suggest that continuing to increase the fishing capacity of small-scale fisheries in the absence of effective and restrictive management actions may exacerbate overexploitation risk.